Kekuatan Pemasaran Sosial Media dalam Minat Beli Sambal Kemasan - Humaidi, Taufiq Rahman; Nugrahaini, Amelia Dwi (Airlangga Journal of Innovation Management, 2025)
Sambal, a type of chili sauce is a popular food product, making it essential for producers to develop the right strategies to boost sales. Social media Marketing was important in introducing products and increasing consumer purchase intention for packaged sambal. Marketing strategies have evolved alongside the advancement of digital technologies. One of the digital technology developments that supports marketing is social media. This study aims to analyze the power of social media advertising on the purchase intention of packaged sambal. Specifically, it investigates the influence of visuals, special offers, music, language, interaction, endorsements, and followers on purchase intention. Data were collected through surveys distributed to 106 social media users. This study uses multiple linear regression analysis and is conducted using SPSS software. The results show that visual elements and the number of followers significantly influence consumer’s purchasing intention. A simple and visually appealing design enhances information comprehension, making it easier for potential buyers to understand product details. Additionally, the high number of followers could increase consumer trust and brand credibility, positively affecting purchase decisions.  On the other hand, factors such as special offers, music, language, interaction, and endorsements did not affect purchase intention significantly. These results provide valuable insights for packaged sambal producers, highlighting the importance of optimizing the social media marketing strategies by focusing on the most effective elements.